Electromyographic analysis of lower limbs during baseball batting - Nakata, H.; Miura, A.; Yoshie, M.; Kanosue, K.; Kudo, K. (The Journal of Strength and Conditioning Research, 2013)
We investigated the muscle activation pattern of lower limbs in baseball batting by recording surface electromyography (sEMG) from 8 muscles, the left and right rectus femoris (RF), biceps femoris (BF), tibialis anterior (TA), and medial gastrocnemius (MG) muscles. The muscle activities were compared between 10 skilled baseball players and 10 unskilled novices. The batting motion was divided into 7 phases: waiting, shifting body weight, stepping, landing, swing, impact, and follow through. The timing for these phases was analyzed by using a high-speed video camera. The onset latencies of sEMG were significantly earlier in baseball players at the left-RF (p < 0.01), right-BF (p < 0.05), and left-BF (p < 0.01). The peak amplitudes of sEMG activity were greater in skilled players at the right-RF (p < 0.01), right-BF (p < 0.01), left-BF (p < 0.01), left-TA (p < 0.01), right-MG (p < 0.01), and left-MG (p < 0.05). The timing for shifting, stepping, and landing was also significantly earlier in skilled players (p < 0.05, p < 0.01, and p < 0.05, respectively). Our findings suggest that preparations for the swing are made earlier in skilled baseball players who recruit their lower muscles for the swing more effectively than novices.